Application of press-coatings for the development of prolonged release tablets based on hygroscopic substances - Yu. M. Kotsur; O. A. Terenteva; E. V. Flisyuk; I. A. Narkevich (Разработка и регистрация лекарственных средств)
Introduction. The development of universal approaches to work with hygroscopic substances is an urgent task of pharmaceutical technology. Coating of tablets with hygroscopic substances deserves special attention. Pressed coatings represent a promising method for coating hygroscopic tablets. Such coating can contribute both to imparting the specified release characteristics to the tablet, and to the protection of APS from environmental factors, as well as can be an alternative to obtaining matrix tablets of prolonged action with hygroscopic substances in those cases when direct contact of APS with the polymeric carrier is undesirable.Aim. Study of the possibility of using pressed coatings to control the kinetics and release site of hygroscopic substances from tablets using DEAE as an example.Materials and methods. The object of the present study was the substance bis{2-[(2Z)-4-hydroxy-4-oxobut-2-enoyloxy]-N,N-diethylethanaminium} butanedioneate (DEAE), shellac (BonuLac®, Biogrund GmbH, Germany); copolymer of methacrylic acid and ethyl acrylate (AquaPolish® 712, Biogrund GmbH, Germany); copolymer of polyvinylpyrrolidone and polyvinyl acetate (Kollidon® SR, BASF, Germany), ethyl cellulose (Acros Organics, USA). Lactose monohydrate (Tablettose® 80, Meggle AG, Germany) was added to the formulations as an excipient. The superdisintegrant crospovidone XL and the lubricant sodium stearyl fumarate (JRS, Germany) were used to improve disintegration.Results and discussion. The properties of the pressed coatings were studied. Shellac-based coating mixture may be suitable for obtaining enteric soluble coating for dissolution in medium with pH 4.5. PVP and PVA copolymer does not provide stability of coatings in acidic medium, but its introduction into formulations with ethyl cellulose, as well as into formulations with copolymer of methacrylic acid and ethyl acrylate allows to achieve uniform release in all media within 5 hours.Conclusion. The study showed the possibility of using pressed coatings to control the kinetics of API release. The coating obtained using this technology can be used for hygroscopic substances. This method is a useful alternative when it is necessary to separate the matrix-forming polymer and the API, which have synergistic hygroscopic properties.